AlphaE Integrin Expression Is Increased in the Ileum Relative to the Colon and Unaffected by Inflammation. (15th June 2018) - Ichikawa, Ryan; Lamb, Christopher A; Eastham-Anderson, Jeff; Scherl, Alexis; Raffals, Laura; Faubion, William A; Bennett, Miriam R; Long, Anna K; Mansfield, John C; Kirby, John A; Keir, Mary E
Abstract: Background: Recent findings suggest that αE expression is enriched on effector T cells and that intestinal αE + T cells have increased expression of inflammatory cytokines. αE integrin expression is a potential predictive biomarker for response to etrolizumab, a monoclonal antibody against β7 integrin that targets both α4β7 and αEβ7. We evaluated the prevalence and localization of αE + cells as well as total αE gene expression in healthy and inflammatory bowel disease patients. Methods: αE + cells were identified in ileal and colonic biopsies by immunohistochemistry and counted using an automated algorithm. Gene expression was assessed by quantitative reverse-transcriptase polymerase chain reaction. Results: In both healthy and inflammatory bowel disease patients, significantly more αE + cells were present in the epithelium and lamina propria of ileal compared with colonic biopsies. αE gene expression levels were also significantly higher in ileal compared with colonic biopsies. Paired biopsies from the same patient showed moderate correlation of αE expression between the ileum and colon. Inflammation did not affect αE expression, and neither endoscopy nor histology scores correlated with αE gene expression. αE expression was not different between patients based on concomitant medication use except 5-aminosalicylic acid. Conclusion: αE + cells, which have been shown to have inflammatory potential, are increased in the ileum in comparison with the colon in both Crohn's disease and ulcerative colitis, as well as in healthy subjects. In inflammatory bowel disease patients, αE levels are stable, regardless of inflammatory status or most concomitant medications, which could support its use as a biomarker for etrolizumab.